Pertanggungjawaban Hukum Pelaku Usaha yang Mendistribusikan Produk Makanan yang Tidak Layak Konsumsi atau Kedaluwarsa - Siregar, Johany; Nachrawi, Gunawan (LITERATUS, 2024)
In food products, it is very important to include information about the expiration date to protect consumers from the dangers of poisoning  from  expired  products.  The expiration date must be written on the product packaging or on the packaging box only. Usually, products that include information about the expiration date are products that come from factories or industries that produce in large quantities and have been widely distributed. However, sometimes there are some manufacturers who deliberately do not include the expiration date on their product packaging for profit alone. The act of selling products that are no longer fit for consumption is an act that is detrimental to consumers and violates the Consumer Protection Act with quite severe sanctions for the community or entrepreneurs who trade them. The formulation of the problem discussed is: 1) What are the legal consequences for business actors who deliberately distribute food products that are not fit for consumption or expired? and 2) What is the legal responsibility of business actors who deliberately distribute food products that are not fit for consumption or expired? The research method used is the normative juridical method, namely analyzing the relationship between applicable laws and regulations with legal theories and the practice of implementing positive law concerning the problems discussed. Keywords: legal responsibility, business actors, distribution of food products, expired